2008
DOI: 10.1096/fj.08-113274
|View full text |Cite
|
Sign up to set email alerts
|

Cysteinyl leukotriene 2 receptor‐mediated vascular permeability via transendothelial vesicle transport

Abstract: Cysteinyl leukotrienes (CysLTs) are potent mediators of inflammation synthesized by the concerted actions of 5-lipoxygenase (5-LO), 5-LO-activating protein (FLAP), leukotriene C(4) synthase, and additional downstream enzymes, starting with arachidonic acid substrate. CysLTs produced by macrophages, eosinophils, mast cells, and other inflammatory cells activate 3 different high-affinity CysLT receptors: CysLT(1)R, CysLT(2)R, and GPR 17. We sought to investigate vascular sites of CysLT(2)R expression and the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 39 publications
2
57
1
Order By: Relevance
“…3B and C) and next examined whether its enhancement is related to arachidonic acid metabolites derived by 5-LO and FLAP, i.e., LTB4 and cysteinyl LTs. Administration of exogenous cysteinyl LTs (LTD4, 500 ng in 100 l PBS, a dose which increases systemic vascular permeability in mice [27]) 10 min before bacterial injection significantly increased E. coli K1 penetration into the brain in cPLA 2 ␣ Ϫ/Ϫ mice (Fig. 7B) without affecting bacterial counts in the blood, kidneys, and spleens ( Fig.…”
Section: Vol 78 2010 Targeting Host Factors In E Coli Meningitis 4305mentioning
confidence: 99%
“…3B and C) and next examined whether its enhancement is related to arachidonic acid metabolites derived by 5-LO and FLAP, i.e., LTB4 and cysteinyl LTs. Administration of exogenous cysteinyl LTs (LTD4, 500 ng in 100 l PBS, a dose which increases systemic vascular permeability in mice [27]) 10 min before bacterial injection significantly increased E. coli K1 penetration into the brain in cPLA 2 ␣ Ϫ/Ϫ mice (Fig. 7B) without affecting bacterial counts in the blood, kidneys, and spleens ( Fig.…”
Section: Vol 78 2010 Targeting Host Factors In E Coli Meningitis 4305mentioning
confidence: 99%
“…Its distribution in the human heart and vasculature, adrenal gland, immune cells, brain, and other tissues (Heise et al, 2000;Nothacker et al, 2000;Kamohara et al, 2001;Evans, 2002) suggests that the CysLT 2 receptor is potentially involved in both physiological and pathophysiological processes. In animal models, we have demonstrated that transgenic expression of the hCysLT 2 receptor in vascular endothelium predisposes to heightened myocardial ischemia-reperfusion injury and increased vascular permeability in certain vascular beds Moos et al, 2008). The CysLT 2 receptor has been implicated in allergic and inflammatory diseases such as asthma, rhinitis, and sinusitis (Pillai et al, 2004;Steinke and Borish, 2004), as well as in cerebral inflammation and edema (Di Gennaro et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Biological activities such as airway hyperresponsiveness [13], cellular adhesion [14][15][16], cell migration [17,18] and mucus secretion [19] are mediated predominantly through cysLT 1 R activation. Whereas cysLT 2 R has been reported to cause vascular permeability [4,20], blockade of cysLT 3 R appears to prevent hypoxic brain injury [12].The 85-kDa cytosolic group IVa phospholipase A2 (gIVaPLA2) is a critical intracellular messenger protein for cellular adhesion and secretion of bioactive lipid mediators in human eosinophils [21,22] and polymorphonuclear leukocytes (PMNs) [16,23]. Activation of gIVaPLA2 causes production of arachidonate metabolites and lysophospholipids [22][23][24][25][26], which are essential for b 2 -integrin adhesion of granulocytes.…”
mentioning
confidence: 99%
“…Biological activities such as airway hyperresponsiveness [13], cellular adhesion [14][15][16], cell migration [17,18] and mucus secretion [19] are mediated predominantly through cysLT 1 R activation. Whereas cysLT 2 R has been reported to cause vascular permeability [4,20], blockade of cysLT 3 R appears to prevent hypoxic brain injury [12].…”
mentioning
confidence: 99%